MENINGKATKAN HASIL BELAJAR PENJASORKES MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD DI SDN 019 PANDAU JAYA KABUPATEN KAMPAR - Rita Delina (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is based on the learning result of physical education of sports and health which is still low. This studyaims to improve student learning outcomes class VI.A Elementary School 019 Pandau Jaya District Siak HuluKampar District. This study uses classroom action research with two cycles by applying the cooperative typemethod Student Teams Achievement Division (STAD). Based on the result of research of students absorption inphysical education lesson of sport and health increase significantly, pratindakan replication result is 43,53 (veryless good); in cycle I was 71,76 (good); and the result of cycle II is 89.71 (very good). The mastery of individual andclassical learning increases; preliminary data 8 students 23,53 (unfinished); in cycle I was 25 students and 73.53%(unfinished); and in cycle II is 33 students and 89,71% (complete). Thus it can be concluded that, the application ofcooperative method of type Student Teams Achievement Division (STAD). Succeeded to improve learning result ofphysical education of sports and health at VIA Elementary School students 019 Pandau Jaya Siak Hulu.